MEASURES TO INCREASE THE INNOVATIVE ATTRACTIVENESS OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Uzbekistan has recognized the importance of innovation in driving economic growth and has taken significant steps to transform the nation into an innovation-driven economy. However, the country still faces significant challenges in fully harnessing its innovative potential and becoming an attractive destination for innovation-driven investment. This article provides an in-depth analysis of the current state of innovation in Uzbekistan and proposes measures to enhance its innovative attractiveness. By examining the existing literature, policies, and initiatives, we identify key areas that require attention and suggest actionable strategies to foster a thriving innovation ecosystem. The proposed measures include improving the regulatory environment, increasing investment in research and development, and strengthening intellectual property protection.